Massification and its Critique in the Nineteenth Century History of Ideas: József Eötvös on Popular Meanings and Public Life - Hanna Orsolya Vincze (Belphégor)
Writing after the failure of the 1848 Hungarian revolution, József Eötvös, himself a prominent politician and novelist, grappled with the sources of the failure and conditions of success of social and political reforms. In his monumental work, The Dominant Ideas of the Nineteenth Century and their Impact on the State, he proposed that in order to understand the behaviour of the masses and design social and political reforms that will have popular support, one needed to understand the meanings people assigned to popular ideas—as opposed to meanings assigned to them by theorists. Popularity, in this approach, had three components: ideas around which people rallied, emotions that connected them to these ideas, and actions people undertook in their name. The way towards understanding these components was to understand the culture of the people in its various manifestations, from popular religiosity to literary and material culture. By re-reading Eötvös’s work focusing on his conception of popular ideas, this paper investigates how the longstanding tension between popularity and the distrust in populism was articulated in a classic of nineteenth century central European political thought.